Regional Integration, Sectoral Adjustments and Natural Groupings in East Asia - Lee, Hiro (2012)
Although East Asian countries were relatively inactive in signing free trade agreements (FTAs) until the end of 1990s, a number of FTAs involving East Asian countries have been signed since the turn of the century. The objective of this study is to compare welfare gains and sectoral adjustments resulting from various FTA scenarios in East Asia using a dynamic global computable general equilibrium (CGE) model. The RCA rankings of commodities with various FTA scenarios and those with the global trade liberalization are correlated to examine how "natural" each grouping would be. The results suggest that the ASEAN+3 FTA, with relatively large welfare gains and small structural adjustments, could be a facilitating intermediate step towards global free trade. Some of the smaller FTAs, such as the ASEAN-China and ASEAN-Korea FTAs, would result in large structural adjustments for ASEAN countries.